STUDI MANAJEMEN ENERGI LISTRIK DAN ANALISIS PELUANG PENGHEMATAN KONSUMSI ENERGI LISTRIK PADA GEDUNG PENGADILAN NEGERI DENPASAR - I Made Surya Ganesputra; l Gusti Ngurah Janardana; I Nyoman Budiastra (Program Studi Teknik Elektro UNUD, 2022)
The intensity of electrical energy consumption at the Denpasar District Court in 2020 is 133.84 kWh/m2/year. Based on the Minister of Energy and Mineral Resources Regulation No. 13 of 2010 on an air-conditioned building, the building is included in the wasteful category. So the Denpasar District Court office must make efforts to save money by conducting energy audits on lamps, coolers (AC), and other equipment. The purpose of this research is to analyze electrical energy opportunities and provide recommendations for savings that can be made. The method used in this research is descriptive quantitative by calculating the IKE of the building. The results of this study obtained the total energy needed in existing conditions (before the LED lamp and AC inverter were replaced) with the assumption that the lamp and air conditioner operated for 8 working hours per day and 24 days per month, the total energy was 140,101,344 kWh/year. Meanwhile, the total energy consumed after replacing the LED lamps and AC inverter is 124,328,448 kWh/year. So that there is a saving of 15,772,896 kWh of electrical energy for one year with a saving of electrical energy costs of Rp. 22,787,102.85 / year. IKE before replacing the LED lamps and AC Inverter is 41.462 kWh / m2 per year in the wasteful category according to the Ministerial Regulation ESDM No. 13 of 2012. Meanwhile, after replacing the LED lamps and AC inverter, the IKE obtained is 36,794 kWh/m2 per year in the wasteful category, but there are savings in electricity consumption and electricity payment costs.